2008
DOI: 10.1021/om800237r
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of Ethene with Styrene Derivatives, Vinyl Ketone, and Vinylcyclohexane Using a (Phosphine−sulfonate)palladium(II) System: Unusual Functionality and Solvent Tolerance

Abstract: A (phosphine-sulfonate)palladium(II) system catalyzes the copolymerization of ethene with a Variety of styrene deriVatiVes, including those with oxygen functionalities. The copolymerizations also proceed in protic solVents, including water, allowing metal-mediated emulsion copolymerization of ethene and styrene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 18 publications
0
45
0
1
Order By: Relevance
“…Drent et al 20 recently disclosed that an ill-defined catalytic system containing a phosphine sulfonate and a palladium complex (tris(dibenzylideneacetone)dipalladium(0) (Pd 2 (dba) 3 ) or palladium(II) acetate (Pd(OAc) 2 )) permits the copolymerization of ethylene and acrylates where the acrylates are incorporated in a main-chain position. Well-defined palladium catalysts containing a phosphine aryl sulfonate ligand were then disclosed by Hearley et al, 21 Goodall et al, 22,23 Kochi et al, 24,25 Liu et al, 26 Skupov et al, 27 Luo et al, 28 Borkar et al 29 and Vela et al 30 Among those reports, acrylate copolymerization with ethylene was only mentioned by Goodall,22,23 Skupov, 27 and Kochi. 24 During the elaboration of this paper, it was recently reported that using a palladium aryl sulfonate catalyst ligated by DMSO instead of pyridine, it was possible to attain very high acrylate incorporations with the possibility of homopolymerizing an acrylate.…”
Section: Introductionmentioning
confidence: 99%
“…Drent et al 20 recently disclosed that an ill-defined catalytic system containing a phosphine sulfonate and a palladium complex (tris(dibenzylideneacetone)dipalladium(0) (Pd 2 (dba) 3 ) or palladium(II) acetate (Pd(OAc) 2 )) permits the copolymerization of ethylene and acrylates where the acrylates are incorporated in a main-chain position. Well-defined palladium catalysts containing a phosphine aryl sulfonate ligand were then disclosed by Hearley et al, 21 Goodall et al, 22,23 Kochi et al, 24,25 Liu et al, 26 Skupov et al, 27 Luo et al, 28 Borkar et al 29 and Vela et al 30 Among those reports, acrylate copolymerization with ethylene was only mentioned by Goodall,22,23 Skupov, 27 and Kochi. 24 During the elaboration of this paper, it was recently reported that using a palladium aryl sulfonate catalyst ligated by DMSO instead of pyridine, it was possible to attain very high acrylate incorporations with the possibility of homopolymerizing an acrylate.…”
Section: Introductionmentioning
confidence: 99%
“…[145,16] . Sen 等 [146] [128] 提高到 3.6% [148] , Rieger 等 [149] [156] , 极性基团插入率为 3%~9%, 催化活性为 1.5×10 4 ~8×10 4 , 共聚物分子量 为 5000~14400; 极性基团嵌入主链的共聚物为半结晶 态, 熔点为 86~112 ℃. 含咔唑的催化剂 248 催化乙烯 与丙烯酸甲酯和丙烯酸共聚分别得到高度线型(支化度 3)和低支化度(支化度 32)共聚物 [157] [160] , 所 得高度线型结构共聚物分子量不高(3×10 3 ), 可能由于 258 膦端叔丁基体积影响导致极性基团插入率降低, 与 259 催化(2.2%~2.7%)相比极性单体插入率仅为 0.2%~ 0.8%.…”
Section: 膦磺酸型催化剂unclassified
“…Pressurization with ethylene results in the diffusion of ethylene through the aqueous phase to the droplets where polymerization takes place, leading to the formation of polymer dispersions. This technique has been successfully implemented not only for the homopolymerization of ethylene, but also for the copolymerization of ethylene with acrylates, CO, norbornenes, styrene and α‐olefins . However, in all cases, a drastic decrease of activity relative to organic solvent polymerizations is observed.…”
Section: Figurementioning
confidence: 99%